Home alone 2 [videorecording (DVD)] : lost in New York - Hughes, John, 1950-2009; Culkin, Macaulay, 1980-; Pesci, Joe; Stern, Daniel, 1957-; Heard, John, 1946-2017; Curry, Tim; Fricker, Brenda; O'Hara, Catherine (Twentieth Century Fox Home Entertainment, 2000)
"Kevin McCallister is ... ready to turn the Big Apple into his own playground. ... The notorious Wet Bandits, Harry and Marv, still smarting from their last encounter with Kevin, are plotting a huge holiday heist. Kevin's ready to welcome them with a battery of booby traps that the bumbling bandits will never forget"--Container.